FRASE ENDOSENTRIK PADA ARTIKEL DI YAHOO EDISI FEBRUARI 2017 - Kasriadi, Kasriadi; Sinaga, Mangatur; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
ABSTRACT: This research is entitled Endocentric Phrases in Yahoo Articles in February 2017. This study aims to describe the types of endocentric phrases and describe the endocentric phrase functions contained in the February 2017 edition of Yahoo. The method used is descriptive analysis method with a qualitative approach. The research data is an endocentric phrase in the February 2017 edition of Yahoo which numbered 206. The results of the study found were (1) 113 coordinative endocentric phrases, (2) 45 attribute-type endocentric phrases, (3) 48 apositive endocentric phrases. In addition, the syntactic function is occupied by endocentric phrases. These functions include: (1) 66 endocentric phrases that occupy the function of the subject, (2) 6 endocentric phrases that occupy the prediket function, (3) 61 endocentric phrases that occupy object functions, (4) 57 endocentric phrases that occupy the information function, (5) 16 endocentric phrases that occupy complementary functions.  Key Words: Syntax, Syntactic Functions, Phrases, Articles, Yahoo